Strategies for Sustainable Business Models for Open Educational Resources - de Langen, F.H.T (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2013)
For several years, the importance of continuous education has been stressed by several governmental and non-governmental institutions (Janssen & Schuwer, 2012; Marshall & Casserly, 2006). Education is seen as important both for personal growth and empowerment for one’s personal wellbeing as well as for developing the required professional capabilities needed in today’s society. In his 2011 State of the Union address President Obama put emphasis on the government’s ambitions to “out-innovate and out-educate” the rest of the world. Almost at the same time, at the Davos World Economic Forum (2011), the urgency of appropriate education was stressed, observing that the current lack of adequately educated people hinders prosperity and economic growth in the near future. The OECD is preparing a proposal to translate these intentions into a concrete policy.